Do Playworkers' Childhood Play Experiences Affect their Playwork Practice?: an exploratory study - Tracey Maegusuku-Hewett (Cardiff Council, 2005)
This mixed method study report presents the views and experiences of 68 playwork professionals across 5 local authorities of South Wales regarding their childhood experiences of play and the impact that these experiences have on them in their adult life and in their playwork practice. Moreover, views are expressed concerning thenature of children’s play today, alongside an exploration of playwork practice, attitudes to non-adult led play, and the benefit of training. This exploratory study provides a useful basis upon which to take stock of the playwork profession’s approach andattitude to practice and non-adult led play and from which the playwork profession can begin to evaluate current framework training courses and consider whether they are still meeting the needs of the students.